An avian outbreak associated with panzootic equine influenza in 1872: an early example of highly pathogenic avian influenza? - Morens, David M. (Blackwell Publishing Ltd, 2010)
Please cite this paper as: Morens and Taubenberger (2010) An avian outbreak associated with panzootic equine influenza in 1872: an early example of highly pathogenic avian influenza? Influenza and Other Respiratory Viruses 4(6), 373–377. Background  An explosive fatal epizootic in poultry, prairie chickens, turkeys, ducks and geese, occurred over much of the populated United States between 15 November and 15 December 1872. To our knowledge the scientific literature contains no mention of the nationwide 1872 poultry outbreak. Objective  To understand avian influenza in a historical context. Results  The epizootic progressed in temporal‐geographic association with a well‐reported panzootic of equine influenza that had begun in Canada during the last few days of September 1872. The 1872 avian epizootic was universally attributed at the time to equine influenza, a disease then of unknown etiology but widely believed to be caused by the same transmissible respiratory agent that caused human influenza. Conclusions  Another microbial agent could have caused the avian outbreak; however, its strong temporal and geographic association with the equine panzootic, and its clinical and epidemiologic features, are most consistent with highly pathogenic avian influenza. The avian epizootic could thus have been an early instance of highly pathogenic avian influenza.